Reviewser – authors’ best friend - Ljiljana Vučković-Dekić (Биомедицинска истраживања, 2013)
Peer Reviews is the accepted method for ensuring that the science reported in the biomedical literature is of the highest quality. Reviewsers, who are always recruited among the most prominent scientists in the field, are the heart of the peer-Reviews system, and no editor can get along without them. Many authors, especially the younger ones, are unaware of the process so important for the final fate of their scientific work. In this educative article, the principles of the peer Reviews system, the role and the place of the Reviewser in the process of publishing, and the professional ethics as well, are explained.
Keywords: peer Reviews system; Reviewsing technique; professional ethics; good scientific practice; good editorial practice